Trends in extent of surgical cytoreduction for patients with ovarian cancer. - Deanna H Wong; Alexandra L Mardock; Erica N Manrriquez; Tiffany S Lai; Yas Sanaiha; Abdulrahman K Sinno; Peyman Benharash; Joshua G Cohen (PLoS ONE)
Purpose To identify patient and hospital characteristics associated with extended surgical cytoreduction in the treatment of ovarian cancer. Methods A retrospective analysis using the National Inpatient Sample (NIS) database identified women hospitalized for surgery to remove an ovarian malignancy between 2013 and 2017. Extended cytoreduction (ECR) was defined as surgery involving the bowel, liver, diaphragm, bladder, stomach, or spleen. Chi-square and logistic regression were used to analyze patient and hospital demographics related to ECR, and trends were assessed using the Cochran-Armitage test. Results Of the estimated 79,400 patients undergoing ovarian cancer surgery, 22% received ECR. Decreased adjusted odds of ECR were found in patients with lower Elixhauser Comorbidity Index (ECI) scores (OR 0.61, p<0.001 for ECI 2, versus ECI≥3) or residence outside the top income quartile (OR 0.71, p<0.001 for Q1, versus Q4), and increased odds were seen at hospitals with high ovarian cancer surgical volume (OR 1.25, p<0.001, versus low volume). From 2013 to 2017, there was a decrease in the proportion of cases with extended procedures (19% to 15%, p<0.001). There were significant decreases in the proportion of cases with small bowel, colon, and rectosigmoid resections (p<0.001). Patients who underwent ECR were more likely treated at a high surgical volume hospital (37% vs 31%, p<0.001) over the study period. For their hospital admission, patients who underwent ECR had increased mortality (1.6% vs. 0.5%, p<0.001), length of stay (9.6 days vs. 5.2 days, p<0.001), and mean cost ($32,132 vs. $17,363, p<0.001). Conclusions Likelihood of ECR was associated with increased medical comorbidity complexity, higher income, and undergoing the procedure at high surgical volume hospitals. The proportion of ovarian cancer cases with ECR has decreased from 2013-17, with more cases performed at high surgical volume hospitals.